The Role of Women in Council on Gender Diversity, and Their Effect on Disclosure of SDGs - Wisnu Setyawan; Siska Wulandari (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
As organizations with an important role in development, corporations are expected to contribute to the Sustainable Development Goals (SDGs). Gender equality is one of the goals of the SDGs. The role of females on board as agents of the company is expected to contribute to gender diversity in the organization and realize the goals of the SDGs, especially SDGs-5 regarding gender equality. This study aims to analyze the role of women in the council on gender diversity and support SDGs-5 on gender organization through internal gender diversity. They use data from 72 corporate sustainability reports in Indonesia published through the NCSR with GRI standards and processed using statistical regression testing. This study indicates that female on board affects gender diversity and supports SDGs-5 disclosure through gender diversity in the organization. The results of this study answer the theoretical gap with the results of previous studies, where female on board directly hurts the SDGs disclosure.